Health-Related Outcomes 3-15 Years Following Ankle Sprain Injury in Youth Sport: What Does the Future Hold?. (January 2022) - Owoeye, Oluwatoyosi B. A.; Whittaker, Jackie L.; Toomey, Clodagh M.; Räisänen, Anu M.; Jaremko, Jacob L.; Carlesso, Lisa C.; Manske, Sarah L.; Emery, Carolyn A.
Background: This study examined the association between youth sport-related ankle sprain injury and health-related outcomes, 3-15 years postinjury. Methods: A historical cohort study in which uninjured controls were cluster-matched with injured cases. The primary outcome was self-reported Foot and Ankle Outcome Score (FAOS). Secondary outcomes included measures of adiposity, validated questionnaires for physical activity, athletic identity, fear of pain, and tests of strength, balance, and function. Results: We recruited 86 participants (median age of 23 years; 77% female); 50 with a time-loss ankle sprain, median of 8 years postinjury, and 36 uninjured controls cluster-matched by sex and sport. Based on mixed effects multivariable regression models, previously injured participants demonstrated poorer outcomes than controls on all 5 FAOS subscales regardless of sex and time since injury, with the largest differences observed in symptoms (−20.9, 99% CI: −29.5 to −12.3) and ankle-related quality of life (−25.3, 99% CI: −34.7 to −15.9) subscales. Injured participants also had poorer unipedal dynamic balance (−1.9, 99% CI: 3.5 to −0.2) and greater fear of pain (7.2, 99% CI: 0.9-13.4) compared with controls. No statistically significant differences were found for other secondary outcomes. Conclusion: At 3-15 years following time-loss ankle sprain injury in youth sport, previously injured participants had more pain and symptoms, poorer self-reported function, ankle-related quality of life, reduced sport participation, balance, and greater fear of pain than controls. This underlines the need to promote the primary prevention of ankle sprains and secondary prevention of potential health consequences, including posttraumatic osteoarthritis. Level of Evidence: Level III, historical cohort study.